Jatropha curcas L. and Pongamia pinnata L. exhibited differential growth and bioaccumulation pattern irrigated with wastewater - Abid, Rafia; Mahmood, Seema; Zahra, Saman; Ghaffar, Shazia; Malik, Mahwish; Noreen, Sibgha (Penerbit Universiti Kebangsaan Malaysia, 2021)
Pakistan currently faces an acute shortage of water, which has increasingly been devastating for the past few decades. In order to mitigate water scarcity, agriculture sector of the country started using wastewater discharged from various industries. The present study aims to assess the impact of fertilizer industry effluent on Jatropha curcas L. and Pongamia pinnata L., which are popular biofuel tree species. Initially, one-year-old saplings were acclimatized in pots, then wastewater was applied in diluted concentrations of effluent using 20 and 40 mL L-1 to the treatment group while control plants were irrigated with tap water. The physico-chemical properties of the effluent showed high values 179 mg L-1 for biological oxygen demand (BOD), 257 mg L-1 for chemical oxygen demand (COD) and 1200 mg L-1 for total dissolved solid (TDS), respectively. Surprisingly, high concentrations of arsenic (15 µg L-1) and cadmium (0.78 mg L-1) were present but chromium (Cr) concentration was found within permissible limit to WHO. The levels applied caused a significant (p≤0.05) increase in plant growth and biomass. The extent of membrane damage assessed via malondialdehyde (MDA) production was also greater in the roots of P. pinnata while reverse was true for shoots of J. curcas. A more profound (p≤0.05) reduction in photosynthetic pigments and carotenoids was observed in P. pinnata at concentrated level of effluent. Overall, the study signifies a 2-folds potential of biofuel tree species for efficient reuse of wastewater, as well as for remediation of metals from wastewater and soil.